Can control theory explain the link between parental physical abuse and delinquency? A longitudinal analysis - Rebellon, Cesar J. (Journal of research in crime and delinquency, 2005)
Although a growing literature suggests that physical abuse is associated with delinquency, little empirical research has attempted to probe the nature of the mechanism that underlies the apparent relationship. Moreover because the theoretical literature tends to invoke learning and strain theories as explanations for the apparent relationship, even less research has attempted to determine whether control theory can account for the link between abuse and delinquency. It remains possible, however that measures of abuse are highly correlated with self-control or that abuse itself promotes delinquency only insofar as it impedes conventional social bonds. The present study attempts to provide a preliminary test of these possibilities using three waves of panel data from a national probability sample. Longitudinal results suggest that abuse contributes to violent offending as well as property offending and that neither self-control theory nor social bonding theory appears capable of explaining the relationship. [ABSTRACT FROM AUTHOR]